ANALISIS PENGARUH VARIABEL MAKROEKONOMI DAN RISIKO GEOPOLITIK TERHADAP PERGERAKAN JAKARTA ISLAMIC INDEX 2014-2024 - Cupian, Cupian; Noven, Sarah Annisa; Rohma, Naili (Universitas Islam Negeri Raden Intan Lampung, 2026)
Utilizing secondary data gathered on a monthly basis spanning 2014–2024 sourced from the Indonesia Stock Exchange, Bank Indonesia, the World Gold Council, and the Geopolitical Risk Index, this investigation employs a quantitative framework. The analytical procedure involved multiple linear regression estimated via Ordinary Least Squares, preceded by stationarity assessments, classical assumption checks, and heteroskedasticity correction through robust standard errors. The objective was to scrutinize the influences of inflation, exchange rates, global gold prices, and geopolitical risk on the Jakarta Islamic Index. Findings reveal that inflation and geopolitical risk exert no statistically significant impact on the index. In contrast, the exchange rate demonstrates a negative and significant effect at the 5% level, whereas global gold prices exhibit a positive and significant effect at the 10% level. Collectively, these four determinants significantly influence the Jakarta Islamic Index. The model's coefficient of determination shows that 10.97% of the index's variability is accounted for, with the remainder attributable to factors beyond the model. These outcomes offer valuable insights for investors making decisions in the Islamic capital market by considering macroeconomic conditions and global risk.